Exploring Minecraft - Hjorth, Larissa. author. aut Link
XIV, 189 p. 31 illus.
Keywords: “Minecraft is undoubtedly one of the most influential games of the past decade. Exploring Minecraft brilliantly situates this multiplatform and multisensory game within today’s pervasive play culture, focusing on its role in players’ everyday lives across domestic and educational spaces, and across cultural and generational contexts. In times of social distancing, Hjorth, Richardson, Davies, and Balmford make a compelling argument for the significance of social play and creativity in everyday life. An essential resource for gamers, educators, academics, and parents interested in the interconnections between games, education, domestic life, and creative practices.” - Adriana de Souza e Silva, North Carolina State University, USA This book directs critical attention to one of the most ubiquitous and yet under-analyzed games, Minecraft. Drawing on three years of ethnographic fieldwork intomobile games in Australian homes, the authors seek to take Minecraft seriously as a cultural practice. The book examines how Minecraft players engage in a form of gameplay that is uniquely intergenerational, creative, and playful, and which moves ambiently throughout everyday life. At the intersection of digital media, quotidian literacy, and ethnography, the book situates interdisciplinary debates around mundane play through the lens of Minecraft. Ultimately, Exploring Minecraft seeks to coalesce the discussion between formal and informal learning, revealing new forms of digital media creativity and ethnographic innovation around the analysis of games in everyday life. Larissa Hjorth is Distinguished Professor and Director of the Design & Creative Practice Platform at RMIT University, Australia. Ingrid Richardson is Professor in the School of Media & Communication at RMIT University, Australia. Hugh Davies is a postdoctoral fellow in the Design & Creative Practice Platform at RMIT University, Australia. William Balmford has a PhD in Media & Communication from RMIT University, Australia.